Analisis Pengelolaan Fasilitas Wisata di Daya Tarik Kapalo Banda Taram Kabupaten Lima Puluh Kota - Anugrah Dipta Adria; Yuliana Yuliana (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
This research aims to analyze the management of tourist facilities in the Kapalo Banda Taram Attraction, Limapuluh Kota Regency. This research is descriptive research with qualitative data and uses a survey method. Data collection techniques in this research are interviews, observation and documentation. informants in this research were the fifty city district tourism offices, the guardian of Nagari Taram, the manager, the Pokdarwis of the Kapalo Banda Taram attraction, visitors and the surrounding community. This research uses a purposive sampling technique. Data analysis was carried out by data reduction, presenting data and drawing conclusions. The results of this research as a whole show that the tourist facilities at the Kapalo Banda Taram Attraction, Limapuluh Kota Regency, have added parking to the main facilities, the management always maintains the cleanliness of the facilities and the management sets regulations for every tourist who visits to maintain the cleanliness of the facilities and always carry out control over every main facility provided, then at the supporting facilities, plans are made to replace the prayer room carpet, ensure the cleanliness of the facility equipment such as washing worship equipment once a week, cleaning the rubbish bins in the morning and always checking the cleanliness of the toilets, finally the supporting facilities are planning to hold The souvenir kiosk previously caught fire, the management is also active in offering existing souvenirs and currently there are no supporting facilities due to the fire.